2012
DOI: 10.1021/nn304872n
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Targeted Deep-Tissue Photodynamic Therapy Based on Near-Infrared Light Triggered Upconversion Nanoconstruct

Abstract: Two major challenges of current photodynamic therapy (PDT) are the limited tissue penetration of excitation light and poor tumor-selectivity of the photosensitizer (PS). To address these issues, we developed a multifunctional nanoconstruct consisting of upconversion nanoparticles (UCNPs) that transform near-infrared (NIR) light to visible light and a photosensitizer zinc(II) phthalocyanine (ZnPc). Folate-modified amphiphilic chitosan (FASOC) was coated on the surface of UCNPs to anchor the ZnPc close to the UC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
367
0
3

Year Published

2014
2014
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 482 publications
(392 citation statements)
references
References 37 publications
9
367
0
3
Order By: Relevance
“…The DL and EE of VP16 in the VP16-SLNs were considered optimum for further experiments. [37][38][39] It was found that the curve of VP16-SLNs showed the characteristic absorption peak at 285 nm, which was the same as that for free VP16 ( Figure 2A). As shown in Figure 2B, the spectra of free VP16, plain SLNs, and VP16-SLNs were obtained.…”
Section: Resultsmentioning
confidence: 89%
“…The DL and EE of VP16 in the VP16-SLNs were considered optimum for further experiments. [37][38][39] It was found that the curve of VP16-SLNs showed the characteristic absorption peak at 285 nm, which was the same as that for free VP16 ( Figure 2A). As shown in Figure 2B, the spectra of free VP16, plain SLNs, and VP16-SLNs were obtained.…”
Section: Resultsmentioning
confidence: 89%
“…Exactly 20,000 cells were analyzed using flow cytometry analysis with analytical flow cytometry instrument (BD FACSVerse). 32,33 The experiments were repeated three times.…”
Section: Detection Of Rosmentioning
confidence: 99%
“…13 The resulting LiYF 4 :Tm 3+ /Yb 3+ -UCNPs showed a diamond-like morphology as evidenced by TEM (Fig. S1, ESI †), and an average size of circa…”
mentioning
confidence: 97%
“…The application of Ln 3+ -UCNPs as an energy source for exciting photosensitizers has been proposed. [8][9][10][11][12][13] The nanoconstructs, which were prepared using upconverting nanoparticles for the excitation of different photosensitizers, made use of the Er 3+ transitions, 2 H 11/2 , 4 S 3/2 -4 I 11/2 and 4 F 9/2 -4 I 11/2 . The transitions have one major disadvantage, the emission from these transitions does not overlap with the strongest absorption peak, the Soret band, of the photosensitizer presently used, which is at B400 nm.…”
mentioning
confidence: 99%